Otolithic Receptor Mechanisms for Vestibular-Evoked Myogenic Potentials: A Review - Curthoys, Ian S.; Grant, J. Wally; Burgess, Ann M.; Pastras, Chris J.; Brown, Daniel J.; Manzari, Leonardo (Frontiers in Neurology, 2018)
Air conducted sound and bone conduced vibration activate otolithic receptors and afferent neurons in both the utricular and saccular maculae, and trigger small electromyographic (EMG) responses (called vestibular evoked myogenic potentials (VEMPs)) in various muscle groups throughout the body. The use of these VEMPs for clinical assessment of human otolithic function is built on the following logical steps: 1. That high frequency sound and vibration at clinically effective stimulus levels activate otolithic receptors and afferents, rather than semicircular canal afferents, and 2. That there is differential anatomical projection of otolith afferents to eye muscles and neck muscles, and 3. That isolated stimulation of the utricular macula induces short latency responses in eye muscles, and that isolated stimulation of the saccular macula induces short latency responses in neck motoneurons. Evidence supports these logical steps, and so VEMPs are increasingly being used for clinical assessment of otolith function, even differential evaluation of utricular and saccular function. The proposal, originally put forward by Curthoys in 2010, is now accepted: that the ocular VEMP (oVEMP) reflects predominantly contralateral utricular function and the cervical VEMP (cVEMP) reflects predominantly ipsilateral saccular function. So VEMPs can provide differential tests of utricular and saccular function, not because of stimulus selectivity for either of the two maculae, but by measuring responses which are predominantly determined by the differential neural projection of utricular as opposed to saccular neural information to various muscle groups. The major question which this review addresses is how the otolithic sensory system, with such a high density otoconial layer, can be activated by individual cycles of sound and vibration and show such tight locking of the timing of action potentials of single primary otolithic afferents to a particular phase angle of the stimulus cycle even at frequencies far above 1000 Hz. The new explanation is that it is due to the otoliths acting as seismometers at high frequencies and accelerometers at low frequencies. VEMPs are an otolith-dominated response, but in a particular clinical condition, semicircular canal dehiscence, semicircular canal receptors are also activated by sound and vibration, and act to enhance the otolith-dominated VEMP responses.